Advances in Optofluidics - Xuming Zhang (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Optofluidics a niche research field that integrates optics with microfluidics. It started with elegant demonstrations of the passive interaction of light and liquid media such as liquid waveguides and liquid tunable lenses. Recently, the optofluidics continues the advance in liquid-based optical devices/systems. In addition, it has expanded rapidly into many other fields that involve lightwave (or photon) and liquid media. This Special Issue invites review articles (only review articles) that update the latest progress of the optofluidics in various aspects, such as new functional devices, new integrated systems, new fabrication techniques, new applications, etc. It covers, but is not limited to, topics such as micro-optics in liquid media, optofluidic sensors, integrated micro-optical systems, displays, optofluidics-on-fibers, optofluidic manipulation, energy and environmental applciations, and so on.